2021
DOI: 10.3390/cancers13153648
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Organization Does Not Influence T-Cell Distribution in Stroma of Human Pancreatic Cancer

Abstract: The dominant intrastromal T-cell infiltration in pancreatic cancer is mainly caused by the contact guidance through the excessive desmoplastic reaction and could represent one of the obstacles to an effective immune response in this tumor type. This study analyzed the collagen organization in normal and malignant pancreatic tissues as well as its influence on T-cell distribution in pancreatic cancer. Human pancreatic tissue was analyzed using immunofluorescence staining and multiphoton and SHG microscopy suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Notably, studies tracking T-cell migration in vivo have highlighted how aligned fibers shape the migratory paths of T-cells within tumor microenvironments, guiding them along collagen fibers and leading to accumulation in the stroma [18,53,54]. Our findings corroborated well with a study using reconstituted collagen matrices with random, partially aligned, and aligned fibrils, which showed that collagen fibril alignment did not influence the directionality of T-cell migration [26]. However, another study reported that T-cell migration directionality is increased in aligned collagen matrices [13].…”
Section: Matrix Alignment Reduces T-cell Migratory Capacitysupporting
confidence: 87%
See 1 more Smart Citation
“…Notably, studies tracking T-cell migration in vivo have highlighted how aligned fibers shape the migratory paths of T-cells within tumor microenvironments, guiding them along collagen fibers and leading to accumulation in the stroma [18,53,54]. Our findings corroborated well with a study using reconstituted collagen matrices with random, partially aligned, and aligned fibrils, which showed that collagen fibril alignment did not influence the directionality of T-cell migration [26]. However, another study reported that T-cell migration directionality is increased in aligned collagen matrices [13].…”
Section: Matrix Alignment Reduces T-cell Migratory Capacitysupporting
confidence: 87%
“…These matrices can be customized in terms of fibril microstructure, crosslinking density, and integration with other ECM molecules [25], enabling the simulation of both homeostatic and pathophysiological conditions. Recent initiatives have utilized 3D collagen matrices with aligned collagen fibrils to study T-cell migration [13, 26], adjustable collagen density to examine T-cell activity [11], and tunable viscoelasticity to modulate T-cell subtypes [27]. However, a comprehensive study to elucidate T-cell activation and functions, alongside a mechanistic exploration of T-cell mechanosensing in response to matrix alterations, is still needed.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation of the ECM and immune cells in clinical samples has also been investigated. Kamionka et al showed the collagen composition in pancreatic tumor tissues was not significantly linked with immune cell infiltration, suggesting collagen organization has a minor impact on T cell distribution [127].…”
Section: Correlation Of Alterations In the "Trinity" Population In Pr...mentioning
confidence: 99%
“….1] 𝑚 x ×𝑚 y , where values specify how cells should be oriented. In case the tumor and the stroma are present in the neighborhood's mask, 𝑀 𝑂𝑟𝑛𝑡𝑡𝑛 is initialized in reference to the location of the tumor so that cells are oriented forming a rim around the tumor border153 (Fig 4.4ab).Cell phenotype mask values in 𝑀 𝑃𝑛 , 𝑀 𝑃ℎ_𝐶𝑒𝑙𝑙𝑠 , and 𝑀 𝑃ℎ_𝑁𝑢𝑐 are updated iteratively by a constrained minimization of ℓ 𝑃 :…”
mentioning
confidence: 99%